Robustness assessment of semi-rigid steel multi-storey frames. (June 2020) - Gomes, Vitor Rodrigues; Tenchini, André; Lima, Luciano; Vellasco, Pedro
Abstract: In recent years, the interest in knowledge and evaluation of the post-critical path of structures has increased mainly due to the recent occurrence of terrorist attacks and other exceptional events. In steel structures, joints play an essential role in the structural behaviour. Therefore, an adequate resistance is vital to prevent progressive collapse. This study presents a numerical evaluation of steel structures with bolted flush endplate semi-rigid joints using models based on finite element method focused on their post-critical nonlinear response. The current investigation addresses the structural behaviour of steel joints centred on the collapse of an internal column scenario. Furthermore, the structure robustness and the steel joints structural response was evaluated, as well as the development of internal stresses. The results were also estimated and compared with the main robustness design codes. The results indicated that the presence of elements able to withstand substantial tension loads is conditioned to an increase of the structural robustness to prevent progressive collapse. Within this perspective, the results also indicated that an increase of the bolt diameter led to an enhanced rotation capacity and ability to sustain gravity loads. Besides, it was noticed that most of the evaluated joints were able to meet the codes criteria to prevent progressive structural collapses.